Proses Kreatif Mahasiswa dalam Menulis Naskah dan Mementaskan Drama di Unit Kegiatan Mahasiswa Teater Oksigen Universitas Muhammadiyah Jember: Proses Kreatif Mahasiswa dalam Menulis Naskah dan Mementaskan Drama di Unit Kegiatan Mahasiswa Teater Oksigen Universitas Muhammadiyah Jember - Anita, giskameditaputri; anggraeni, Dr. Astri Widyaruli; Citraningrum, Dina Merdeka (Universitas Negeri Surabaya, 2025)
This study aims to analyze the creative process of students in writing scripts and performing dramas at the Oksigen Theater Student Activity Unit (UKM) of the Muhammadiyah University of Jember. This study highlights the process of writing scripts, drama practice, drama performance days and reflections. The research method used is descriptive qualitative. The data source comes from Oksigen Theater UKM students who are experienced in performing drama performances. The data analyzed is the creative process of Oksigen students in performing drama performances. The author collected data using structured interview techniques, selected observations and documentation. The results of the study indicate that the creative process of Oksigen Theater UKM involves two stages, namely scriptwriting and the performance process. The scriptwriting process begins with in-depth research, field surveys, and refinement through script analysis. In performing a performance, it is necessary to practice with several stages and preparation for the performance and end with reflection. The creative process carried out by Oksigen Theater UKM students is relevant to be a reference in the process of presenting drama performances.